Generation of clonal microplants and hairy root cultures of the aromatic medicinal plant Salvia runcinata L.f. - Figlan, Sandiswa (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2012.